Rekaan Versatil Permainan Kanak-Kanak Prasekolah - Nurul Najihah, Yusoff (Universiti Malaysia Sarawak (UNIMAS), 2016)
The versatile design of play for preschool kids is a design which made specially with dwifunction. This research was dine since this kinds of versatile design of play preschool kids can rarely be found in the market. Play or game is an action which is chosen without any kind of force, without being forced of any responsibility or any particular purposes. The purpose of the play depends on the game itself an it could only be gained when they play the game. Kids love to play because within themselves there is the influence of inner self and the influence improve themselves. According to Hurlock(1993), the age of preschool kids (3-6 years) is (golden age) which is in the process of kid's development because during this age kids are going through the process of physical development, intelectual, emotional and social,